(untitled) (Journal of Accounting and Financial Studies ( JAFS ), 2022)
The research aims to achieve a set of objectives, the most important of which is determining the extent to which the auditors of the research sample in the Federal Bureau of Financial Supervision adhere to the requirements of the quality control system according to the Iraqi Audit Manual No. The federal financial / research sample with the quality control system according to the Iraqi audit guide No. 7), and the researcher seeks to test the main research hypothesis and sub-hypotheses, and to achieve this, a questionnaire was designed by (Google Form) and distributed electronically to the elements of the research sample, Through the statistical package program (SPSS), the results of the questionnaire were analysed. In light of the applied aspect of the research, a number of conclusions were reached, the most important of which are: Existence of policies and procedures in the quality control system designed by the Federal Office of Financial Supervision that give reasonable assurance that auditors comply with the standards and rules of ethical and professional behaviour, The researcher made a number of recommendations, including: Allocating an auditor and his assistants for each audit task to be implemented, with conditions defining the features and characteristics of the head and members of the work team that are compatible with the nature of the audit process entrusted to them to perform.